Arduino UNO Application for Temperature Control Chicken Eggs Incubator Machine - Rufinus Nainggolan; Idham Kamil; Al Qadry; Marlon Tua Pangihutan Sibarani; Dohar Sinabutar; Berta Br. Ginting (P3M Politeknik Negeri Bengkalis, 2025)
Poultry animals such as chickens incubate their eggs in three weeks to hatch their eggs, which sometimes the egg yields are not optimal so that a poultry egg incubator and its system are needed to optimize the results of hatching in which this built-in incubator with a capacity of 300 eggs with a rack system that rotates automatically based on Arduino Uno, using a digital temperature and hygrometer sensor so that the temperature can be set at 38-39 0C and the humidity can be set at 55-70% according to the egg hatching temperature and humidity, and from the test results obtained, the number of eggs that do not hatch and hatch both that hatch normally, defective, and die, the research conducted, for chicken eggs, which originally amounted to 300 eggs to be hatched, 291 eggs that hatched well, 5 defective eggs, and 3 eggs that died and 1 egg that does not have any embryos, and the result that this chicken egg incubator machine is capable of hatching eggs 97%.